The Role of the National Commission on Disability in Promoting Business Inclusion for Persons with Disabilities in Indonesia - Andi Muhammad Rivai; Siti Syarifah Wafiqah Wardah; Yusi Irensi Seppa (International Journal of Education, Vocational and Social Science, 2025)
This study analyzes the role of the National Disability Commission in promoting business inclusivity for persons with disabilities in Indonesia. Based on Law No. 8 of 2016, the National Disability Commission serves to ensure the fulfillment of the rights of persons with disabilities, particularly access to employment and entrepreneurship. Using a descriptive qualitative method, this study found three main roles of the National Disability Commission: policy advocacy, cross-sector collaboration, and empowerment through training and public campaigns. Key challenges include weak coordination, limited authority, and social stigma. The National Disability Commission functions as a moral parliament that strengthens the bargaining position of persons with disabilities in the world of work and has the potential to be a catalyst for transformation towards an inclusive and equitable employment ecosystem.